Manajemen Sumber Daya Manusia Pegawai Negeri Sipil Dalam Rangka Reformasi Birokrasi Di Kabupaten Semarang - Pardede, Annetta Carolina; Mustam, Mochammad (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2017)
HR apparatus is a dynamic dimension compared to managing other resources. Humans have different traits, characters, motivations, and emotions that require different handling / management for each personality. Human resources are the most important resource in any organization, where humans are the drivers and managers of other resources. Therefore, one of the responsibilities of the organization is to acquire, organize, motivate, and control its human resources to achieve organizational progress effectively so that bureaucracy in public organizations such as Semarang District Government needs to be managed optimally in the framework of bureaucratic reform. This research is a kind of qualitative research. Sources of data for this study are primary data obtained from interviews with resource persons and informants. Data analysis is done by data reduction, data presentation and conclusion. Based on the result of the research, it can be concluded that the Local Government of Semarang Regency through BKD of Semarang Regency attempts to manage human resources of civil servants in the framework of bureaucratic reform in Semarang regency which includes the arrangement of employee recruitment system, job analysis, job evaluation, standard competency composition, Individual based on competence, application of individual performance appraisal system, development / development of employee database, and development of competency-based employee training.